Eosinophilic granulomatous polyangiitis with IgG4 hypergammaglobulinaemia and salivary gland swelling. Issue 4 (30th March 2020) - Takahashi, Koichiro; Sadamatsu, Hironori; Tashiro, Hiroki; Kato, Go; Uchida, Masaru; Sueoka‐Aragane, Naoko
Abstract: A 51‐year‐old woman was admitted to our hospital for cough, fever, purpura in the legs, and salivary gland swelling. Six years ago, she had been diagnosed with bronchial asthma and was treated with a combination of inhaled corticosteroid and long‐acting beta2‐agonist. Blood examination showed increased eosinophils at 3027 cells/μL and elevated levels of immunoglobulin (Ig) G4 at 261 mg/dL and C‐reactive protein at 2.76 mg/dL. Chest radiograph and computed tomography (CT) showed infiltrates in the bilateral lower lobes. Neck CT showed bilateral salivary gland swelling. Pathological examinations of the lungs and skin purpura showed granuloma with eosinophilic infiltration and perivascular dermatitis, respectively. She was diagnosed with eosinophilic granulomatous polyangiitis (EGPA) and treated with corticosteroids, which resolved the eosinophilia, salivary gland swelling, elevated IgG4 titre, and lung infiltration. As our patient did not meet the American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) 2019 criteria of IgG4‐related disease, the diagnostic was EGPA with IgG4 hypergammaglobulinaemia and salivary gland swelling. Abstract : We present a case of a 51‐year‐old Japanese woman diagnosed with eosinophilic granulomatous polyangiitis (EGPA), a rare vasculitis that can occur in patients with eosinophilia and history of asthma, allergic rhinitis, and sinusitis, with immunoglobulin (Ig) G4 hypergammaglobulinaemia and salivary gland swelling.